Strategi Penerapan Prinsip ESG (Environmental, Sosial and Governance) untuk Pertanian Berkelanjutan Kabupaten Kudus - Nazil Afifatun Nikmah (Soegijapranata Catholic University, 2026)
This study discusses integration of ESG (Environmental, Social and Governance) principles at agricultural sector in Kudus Regency. Through a qualitative approach, this study analyzes the potential and challenges of implementing ESG principles in agricultural systems, as well as how these principles can promote environmental, social and governance. The results of the study show that the agricultural sector of Kudus Regency includes several main commodities such as rice, corn, plantation crops and horticulture which have an important role as economic support for rural communities. However, the sector faces serious challenges in the form of urbanization, limited access to capital, low adoption of modern technology, natural disasters and marketing barriers. ESG principles are offered as a strategic framework in order to answer these challenges. In the environmental aspect, the strategy is directed at environmentally friendly agricultural practices, the use of precision agricultural technology, and the integration of agricultural waste to support the circular economy. In the social aspect, strengthening the capacity of farmers, increasing the participation of village communities, and expanding digital-based market access are the main focuses. Meanwhile, in the aspect of governance, there is a need for regional policies that encourage reasonable pricing policies, multi-stakeholder collaboration, and the provision of access to inclusive financing. With these steps, it is hoped that agriculture in Kudus Regency will have the opportunity to play a strategic role in realizing inclusive and sustainable development.Keywords: ESG Principles; Sustainable Agriculture; Inclusive Development